Einige Fragen der Flächentheorie - Vosylius, R. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Восилюс. Некоторые вопросы теории поверхностейR. Vosylius. Kai kurie paviršių teorijos klausimai